2021
DOI: 10.1111/imr.13042
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for endogenous retroviruses in immune epigenetic regulation*

Abstract: In recent years, there has been significant progress toward understanding the transcriptional networks underlying mammalian immune responses, fueled by advances in regulatory genomic technologies. Epigenomic studies profiling immune cells have generated detailed genome‐wide maps of regulatory elements that will be key to deciphering the regulatory networks underlying cellular immune responses and autoimmune disorders. Unbiased analyses of these genomic maps have uncovered endogenous retroviruses as an unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 173 publications
(187 reference statements)
0
17
0
Order By: Relevance
“…So, the presentation of HERV `self-antigens` can favor the T and B cells to become immunologically aware of the existence of endogenous retroelements, and maybe avoid the development of some diseases, mainly autoimmune diseases. However, it was also reported that the host responses to several types of infectious agents, by increasing the transcriptional induction of endogenous retroelements, can rise the responses of T cells and B cells for these retroelements ( 78 , 79 ).…”
Section: Factors That Contribute For Hervs Expressionmentioning
confidence: 99%
“…So, the presentation of HERV `self-antigens` can favor the T and B cells to become immunologically aware of the existence of endogenous retroelements, and maybe avoid the development of some diseases, mainly autoimmune diseases. However, it was also reported that the host responses to several types of infectious agents, by increasing the transcriptional induction of endogenous retroelements, can rise the responses of T cells and B cells for these retroelements ( 78 , 79 ).…”
Section: Factors That Contribute For Hervs Expressionmentioning
confidence: 99%
“…Collectively, the presence of HERVs in cCREs that are based in experimental data, suggest that HERV sequences may impact, in different degree, the epigenetic regulation of 4 out 5 human genes. The fact that HERVs contain an abundance of regulatory elements [ 66 , 67 , 68 ] and are actively transcribed in humans [ 69 ] strengthen the possible impact of the above finding. It should be noted that the regulatory potential of HERVs sequences may also involve viral transcription factors.…”
Section: Discussionmentioning
confidence: 98%
“…Transposable elements (TEs), which occupy half of the human genome, play critical roles as cis-regulatory elements in various human biological processes (Bourque, 2009; Bourque et al, 2018; Chuong et al, 2017). Notably, a particular subclass of TEs, Endogenous Retroviruses (ERVs), are derived from ancient retrovirus, suggesting a potential association with infection and immunity (Buttler and Chuong, 2021; Kassiotis and Stoye, 2016; Srinivasachar Badarinarayan and Sauter, 2021). Confirming this, an ERV family, MER41, was found to be co-opted as cis-regulatory elements in the primate innate immune response (Bogdan et al, 2020; Chuong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%